2020
DOI: 10.7577/njsr.3327
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Experiences of Violence and Abuse in Same-sex Relationships: Understandings and Challenges

Abstract: Studies on youth intimate partner violence (IPV) issues have been increasingly published during the last few years. However, research on IPV in same-sex relationships among youths is limited. The aim of this article is to expand this knowledge base by exploring the voices of four youth exposed to IPV in same-sex relationships, investigating the similarities to violence in heterosexual relationships and shedding light on the complicating factor of sexuality. The Listening Guide analysis used in this article rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Examples of this included break-ups, conflicts, jealousy, misunderstandings within intimate relationships, and the loss of other relationships, such as important friendships. In line with relationship difficulties being cited as a consequence of experiencing DDA/DDV in the literature reviewed here, it has been suggested that adolescents who have experienced violence in a relationship have an increased risk of perpetrating violence in relationships and engaging in intimate relationships in which mutual violence takes place ( Cutter-Wilson & Richmond, 2011 ; Øverlien, 2020 ; Park et al, 2018 ). Overall, the review presented in this article indicates that experiencing DDA/DDV as a child or adolescent can have severe health-related short- and long-term consequences.…”
Section: Discussionsupporting
confidence: 57%
“…Examples of this included break-ups, conflicts, jealousy, misunderstandings within intimate relationships, and the loss of other relationships, such as important friendships. In line with relationship difficulties being cited as a consequence of experiencing DDA/DDV in the literature reviewed here, it has been suggested that adolescents who have experienced violence in a relationship have an increased risk of perpetrating violence in relationships and engaging in intimate relationships in which mutual violence takes place ( Cutter-Wilson & Richmond, 2011 ; Øverlien, 2020 ; Park et al, 2018 ). Overall, the review presented in this article indicates that experiencing DDA/DDV as a child or adolescent can have severe health-related short- and long-term consequences.…”
Section: Discussionsupporting
confidence: 57%
“…This article demonstrates how young people with sexually abusive relationship experiences describe and interpret their abusive partners, and how these understandings are interlaced with emotional contradictions. Evidence is emerging of how young victimized people may feel trapped in and bound to abusive or violent relationships in similar ways to adult victims (Davies, 2019;Toscano, 2014;Överlien, 2020). We suggest that the emotional dissonance our participants related in stories of their victimization demanded considerable emotion work (Hochschild, 1979) on their part, and this narrowed their opportunities to leave harmful relationships.…”
Section: Discussionmentioning
confidence: 86%
“…Albeit not extensively, I-Poems have been used in research with CYP (and specifically within longitudinal research conducted with this population), most notably by Edwards and Weller (2012) , as well as with young people experiencing disability or whom are vulnerable or marginalised in some way ( Buck et al, 2017 ; Burke et al, 2019 ). For example, McDermott et al (2020) draw on I-Poems within their work with LGBT young people in order to demonstrate ‘I-Feel’ methodology; whilst Mountz (2018) used I-Poems as a lens through which to explore the disproportionate representation of LGBTQ youth within girl's detention facilities in the juvenile justice system in New York, and their experiences while incarcerated, and Øverlien (2020) explored young people's experiences of violence and abuse in same-sex relationships. To our knowledge, I-Poems or poetic inquiry more broadly has not been harnessed in published literature to explore young people's experiences of (and emotional responses to) the pandemic.…”
Section: Introductionmentioning
confidence: 99%